2018
DOI: 10.1016/j.bbamcr.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B core protein promotes liver cancer metastasis through miR-382-5p/DLC-1 axis

Abstract: The hepatitis B virus core protein (HBc), also named core antigen, is well-known for its key role in viral capsid formation and virus replication. Recently, studies showed that HBc has the potential to control cell biology activity by regulating host gene expression. Here, we utilized miRNA microarray to identify 24 upregulated miRNAs and 21 downregulated miRNAs in HBc-expressed HCC cells, which were involved in multiple biological processes, including cell motility. Consistently, the in vitro transwell assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 36 publications
5
29
0
Order By: Relevance
“…Moreover, there is compelling evidence that DLC-1 inhibits tumour metastasis. Du et al demonstrated that miR-382-5p/DLC-1 regulated the migration and invasion of liver cancer [33]. Therefore, we investigated whether DLC-1 regulates colorectal cancer metastasis.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, there is compelling evidence that DLC-1 inhibits tumour metastasis. Du et al demonstrated that miR-382-5p/DLC-1 regulated the migration and invasion of liver cancer [33]. Therefore, we investigated whether DLC-1 regulates colorectal cancer metastasis.…”
Section: Discussionmentioning
confidence: 94%
“…Both in vitro and in vivo experiments show the hepatitis B virus core protein promotes HCC cell migration and metastasis by upregulating miR‐382‐5p, which in turn leads to downregulation of DLC1, and this is further validated in clinical HCC samples (Du et al, ).…”
Section: The Function and Signal Pathways Dlc1 Involvesmentioning
confidence: 93%
“…The mature gene locus were chr14:101,054,316-101,054,337, and the base sequence was GAAGUUGUUCGUGGUGGAUUCG , with a length of 22 nt. (Fig.1) 2.1.2 hsa-miR-382-5P participates in disease regulation Using PubMed to retrieve the related literature of miR-382-5P, we found that miR-382-5P was upregulated in acute promyelocytic leukemia [7,8] , atherosclerosis [12] ,breast cancer [4] ,epidural fibrosis [10] , primary myelofibrosis [9] , primary liver cancer [11] ,cervical cancer [13] , but down-regulated in glioma [5,6] ,oral squamous cell carcinoma [3] ,miR-382 was down-regulated in non-small cell lung cancer [14,15] , osteosarcoma [16] , prostate cancer [19] ,ovarian cancer [20] , primary liver cancer [24] , colorectal cancer [21,22] , while schizophrenia [25] ,diabetic nephropathy [17] , IgA nephropathy [18] ,infantile hemangioma [23] . Thus, the expression of miR-382-5P is tissue-specific, and it is involved in the regulation of cell viability, migration, invasion, angiogenesis, proliferation, cell differentiation, oxidative stress and other biological behaviors.…”
Section: Data Analysis Of Tcga Databasementioning
confidence: 99%
“…A series of nucleases obtained mature miR-382-5P and miR-382-3P by cutting and editing miR-382, in which miR-382-5P was located in the long arm of chromosome 14. In recent years, many studies have shown that the expression of miR-382-5P is abnormal in oral squamous cell carcinoma [3] ,breast cancer [4] ,glioma [5,6] ,acute promyelocytic leukemia [7,8] ,primary myelofibrosis [9] ,epidural fibrosis [10] ,primary liver cancer [11] ,atherosclerosis [12] ,cervical cancer [13] ,miR-382 is abnormal in non-small cell lung cancer [14,15] , osteosarcoma [16] , diabetic nephropathy [17] , IgA nephropathy [18] prostate cancer [19] ,ovarian cacner [20] ,colorectal cancer [21,22] ,infantile hemangioma [23] ,primary liver cancer [24] ,schizophrenia [25] , which are closely related to the proliferation, differentiation, migration, invasion, drug resistance and other biological processes of tumor cells. However, the expression and clinical significance of miR-382-5P in ovarian cancer have not been reported.…”
Section: Introductionmentioning
confidence: 99%